IMPLEMENTASI MAKNA FILIPI 2:2 PADA ANAK SEKOLAH MINGGU MELALUI PERMAINAN TRADISIONAL MENARA BOY: Implementation of Philippians 2:2 in Sunday School Children Through The Traditional Game Menara Boy - Mieke Yen Manu; Junaity Soften Sine; Friandry W. Thoomaszen (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Children's ministry at church must be taken seriously by all related parties. Children should be taught to know God through effective Bible teaching. Designing instructional media at Sunday Schools is unavoidable. The purpose of this community service was to help the church use a traditional game, 'Menara Boy', to implement the meaning of Philippians 2:2 concerning teamwork to achieve a common goal and introduce the younger generation to traditional games. The community service was conducted in two phases: Bible teaching and implementation through playing the game. The result taught children to love and help each other as a family of God. This teaching was effectively implemented when playing 'Menara Boy'—based on the reflections at the end of the game, children admitted that their failure in the game was caused by focusing on themselves and failing to work with others as a team. Therefore, the community service team will recommend using other traditional games as instructional media if the game contains positive values according to the truth of God's Word.